Effect of stage duration on maximal heart rate and post-exercise blood lactate concentration during incremental treadmill tests - Machado, F. A.; Kravchychyn, A. C. P.; Peserico, C S.; da Silva, D. F.; Mezzaroba, P. V. (Journal of Science and Medicine in Sport, 2013)
Objectives This study compared the responses during maximal incremental treadmill tests of 1-min, 2-min, and 3-min stage durations mainly in terms of maximal heart rate (HRmax) and peak blood lactate concentration (LApeak). Design Repeated-measures. Methods Thirty-four male, recreational, endurance-trained runners (40 ± 13 years) performed three tests on a motorized treadmill. The tests started at 8 km h-1 with increments of 1 km h-1 every 1 min for the short-stage protocol, every 2 min for the intermediate-stage protocol, and every 3 min for the long-stage protocol. LApeak was defined for each subject as the highest value among the lactate concentrations determined at the end of each test and at the third, fifth and seventh minutes after test, during passive recovery. Results Analysis of variance revealed a significant effect of the stage duration on the HRmax (p = 0.003) and LApeak (p = 0.001). The HRmax was higher in the intermediate-stage compared to the short-stage protocol (184.8 ± 12.7 vs. 181.8 ± 12.1 beats min-1, p < 0.001), but no significant differences were found between the long-stage (183.1 ± 12.1 beats min-1) and the intermediate-stage or short-stage protocols (p > 0.05). The LApeak was lower in the long-stage compared to the short-stage and intermediate-stage protocols (7.9 ± 2.2 vs. 9.4 ± 2.2 and 9.2 ± 1.9 mmol L-1, respectively, p < 0.05). Further, blood lactate reached peak concentration at the fifth minute after test for all the protocols. Conclusions Thus, HRmax and LApeak depend on the stage duration of the incremental test, but the moment at which blood lactate reaches peak concentration is independent of the duration. Further, we suggest 2-min stage duration protocols to determine HRmax.